Increased Fibrinolysis as a Specific Marker of Poor Outcome After Cardiac Arrest. Issue 10 (October 2018) - Buchtele, Nina; Schörgenhofer, Christian; Spiel, Alexander O.; Jilma, Bernd; Schwameis, Michael
Abstract : Objectives: Recent data suggest that early increased fibrinolysis may be associated with unfavorable prognosis in cardiac arrest. The current study aimed to assess whether there is an optimal fibrinolysis cutoff value as determined by thrombelastometry at hospital admission to predict poor outcome in a cohort of adult patients with out-of-hospital cardiac arrest. Design: Prospective observational cohort study. Setting: Emergency department of a 2.100-bed tertiary care facility in Vienna, Austria, Europe. Patients: Patients with out-of-hospital cardiac arrest of presumed cardiac origin, subjected to targeted temperature management, who had achieved return of spontaneous circulation at admission were analyzed. Interventions: None. Measurements and Main Results: Fibrinolysis was assessed by thrombelastometry at the bedside immediately after hospital admission and is given as maximum lysis (%). The outcome measure was the optimal cutoff for maximum lysis at hospital admission to predict poor outcome (a composite of Cerebral Performance Category 3–5 or death) at day 30, assessed by receiver operating characteristic curve analysis. Seventy-eight patients (61% male, median 59 yr) were included in the study from March 2014 to March 2017. Forty-two patients (54%) had a poor 30-day outcome including 23 nonsurvivors (30%). The maximum lysis cutoff at admission predicting poor 30-day outcome with 100% specificity (95% CI, 90–100%) was greater than or equal to 20%. Tissue-type plasminogen activator antigen levels were likewise elevated in patients with poor neurologic outcome or death 52 ng/mL (interquartile range, 26–79 ng/mL) versus 29 ng/mL (interquartile range, 17–49 ng/mL; p = 0.036). Conclusions: Increased fibrinolysis at admission assessed by thrombelastometry specifically predicts poor outcome in cardiac arrest with presumed cardiac etiology. Abstract : Supplemental Digital Content is available in the text.